At Westonci.ca, we make it easy to get the answers you need from a community of informed and experienced contributors. Get immediate and reliable solutions to your questions from a community of experienced experts on our Q&A platform. Get precise and detailed answers to your questions from a knowledgeable community of experts on our Q&A platform.
Sagot :
Step-by-step explanation:
For y = x², y = 0 when x = 0.
For y = (x + 14)², y = 0 when x = -14.
Notice that the zero of the function has went from 0 to -14, or 14 units to the left.
The answer is "Shift the graph of y = x² left 14 units.".
Answer:
We conclude that the graph y = x² can be transformed into the graph of the given equation y = (x + 14)² by shifting the graph of y = x² left 14 units.
Step-by-step explanation:
Please check the attached graph.
- The blue graph is representing the graph of y = x².
- The red graph is representing the graph of y = (x + 14)².
If we carefully analyze the given graph which is attached below, it is clear that the given graph y = (x + 14)² is the transformed image of form f(x+b) of parent graph y = x².
In this graph, the function y = x² has been moved over 14 units to the left.
In other words,
f(x+2) = f(x+14)² means the function f(x) is shifted 14 units to the left.
Therefore, the graph y = x² can be transformed into the graph of the given equation y = (x + 14)² by shifting the graph of y = x² left 14 units.
![View image absor201](https://us-static.z-dn.net/files/da2/b39a3beb544b72e80d8e7d189ec92e8e.png)
Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. We hope this was helpful. Please come back whenever you need more information or answers to your queries. Keep exploring Westonci.ca for more insightful answers to your questions. We're here to help.